Computational Surgery and Dual Training - Garbey, Marc.; Bass, Barbara Lee.; Collet, Christophe; Mathelin, Michel; Tran-Son-Tay, Roger; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The new and emerging field of computational surgery will improve the efficiency and quality of surgery and will give patients access to very complex surgical operations that require extreme precision and minimum intrusion. In order to effectively deploy computational surgery techniques in life threatening cases such as inoperable cancer tumors that have invaded critical artery tissues or the nervous system, surgeons will have to become very familiar with computing methods, such as image analysis, augmented reality and robotics. Computational Surgery and Dual Training provides the necessary background in computer and surgical techniques that will enable computer scientists/biomedical engineers and surgeons to work together to improve interventional procedures and surgeries. The book brings together contributions from leading minds in the field, who also: Provide a foundation in surgical methods for biomedical engineers who wish to do research in the surgical area Include material on surgery applications and biomedical modeling Offer a detailed discussion of imaging and optimization in computational surgery Computational Surgery and Dual Training is the perfect book for biomedical engineers and active surgeons interested in learning more about these developing methods. .
Computer Assisted Management of Disease and Surgery -- Breast-Conserving Therapy for Breast Cancer: Targets for Investigation to Improve Results -- Changing Paradigms in the Management of Peripheral Vascular Disease: The Need for Integration of Knowledge, Imaging, and Therapeutics -- Image Processing and Diagnostics -- Brain MRI Segmentation -- Knowledge-Driven Recognition and Segmentation of Internal Brain Structures in 3D MRI -- New Dimensions in Diagnostic Imaging of the Aorta -- Methodological Advances on Pulse Measurement through Functional Imaging -- Parallel Multispectral Image Segmentation for Computer Aided Thyroid Cytology -- Image Driven Intervention and Robotics -- Computer-Assisted Digestive Surgery -- Design of a Robotized Flexible Endoscope for Natural Orifice Transluminal Endoscopic Surgery -- MRI-Guided Robot-Assisted Interventions: An Opportunity and a Challenge in Computational Surgery -- Image-Guided Interventions and Robotics -- Modeling, Simulation and Experimental Data -- Emerging Mechanisms of Vein Graft Failure: The Dynamic Interaction of Hemodynamics and the Vascular Response to Injury -- Modeling and Role of Leukocytes in Inflammation -- Multi-modality Imaging for the Simulation of Cerebral Aneurysm Blood Flow Dynamics -- Training -- A Computational Framework for Breast Surgery: Application to Breast Conserving Therapy -- Simulators in Training -- A Computational Desk for Surgeons.
Keywords: Engineering; Minimally invasive surgery; Biomedical engineering; Engineering; Biomedical Engineering; Signal, Image and Speech Processing; Minimally Invasive Surgery; Electronic books